REIT Liquidity Management and Institutional Investors. Issue 4 (1st October 2016) - An, Heng; Wu, Qun; Zhang, Ting
Abstract : We examine how institutional investors influence the liquidity choice between cash versus bank credit lines of real estate investment trusts (REITs). While cash offers REIT managers unconditional control rights, credit lines subject managers to bank monitoring. We find that REITs use more bank credit lines relative to cash under the oversight of institutional investors, especially independent and long-term institutions. These findings suggest that institutional investors attenuate the REIT managers' propensity to keep excessive cash relative to credit lines. Moreover, institutional investors delegate more agency monitoring to banks when their holding REITs are more risky and have more severe agency problems.